2014
DOI: 10.3389/fimmu.2014.00417
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in HIV Vaccine Research for Treatment and Prevention

Abstract: Many attempts have been made or are ongoing for HIV prevention and HIV cure. Many successes are in the list, particularly for HIV drugs, recently proposed also for prevention. However, no eradication of infection has been achieved so far with any drug. Further, a residual immune dysregulation associated to chronic immune activation and incomplete restoration of B and T cell subsets, together with HIV DNA persistence in reservoirs, are still unmet needs of the highly active antiretroviral therapy, causing novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 88 publications
0
48
0
Order By: Relevance
“…That said, even administered in the context of cART, therapeutic immunization is likely to have little efficacy if used without other concomitant immunotherapies due to the immunocompromised status of chronically HIV-1-infected patients. 20 In a study we recently conducted, we hypothesized that HIV-1-specific responses would be enhanced by the administration of cytokines and recombinant human growth hormone (rhGH) in chronic treated HIV-1 infection. 17 Timing and delivery route of immunization were carefully considered in order to achieve the most robust antigen-specific responses.…”
Section: Essential Role Of Therapeutic Vaccines To Provide Antigenic mentioning
confidence: 99%
See 2 more Smart Citations
“…That said, even administered in the context of cART, therapeutic immunization is likely to have little efficacy if used without other concomitant immunotherapies due to the immunocompromised status of chronically HIV-1-infected patients. 20 In a study we recently conducted, we hypothesized that HIV-1-specific responses would be enhanced by the administration of cytokines and recombinant human growth hormone (rhGH) in chronic treated HIV-1 infection. 17 Timing and delivery route of immunization were carefully considered in order to achieve the most robust antigen-specific responses.…”
Section: Essential Role Of Therapeutic Vaccines To Provide Antigenic mentioning
confidence: 99%
“…20,24 Given the renewed interest in therapeutic vaccines as a component of latency reversal strategies, it is of utmost importance to determine the optimal timing and route of administration, in addition to the choice of immunogen.…”
Section: Hiv-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Significant advance in chemotherapy has made HIV-1 infection as a chronic manageable disease in developed countries. Another arm of intervention, a vaccine against HIV-1, is unfortunately not with us yet [1,2]. However, our understanding of the structure of the envelope protein (Env) of HIV-1, a major target of vaccine, is significantly advanced in recent years.…”
mentioning
confidence: 99%
“…The reason to start the treatment having the number of 350-500 cells / µl CD4-lymphocytes or more appears neurocognitive disorders, kidney disease, the presence of a tumor, chronic viral hepatitis B and C, autoimmune, and cardiovascular diseases [7]. Drug treatment should consider the peculiarities of the use of different classes of antiviral drugs: nonnucleoside reverse transcriptase inhibitors (NNRTIs), nucleoside reverse transcriptase inhibitors (NRTIs), protease inhibitors (PIs), fusion inhibitors, CCR5 antagonists (CCR5s) (inhibitors of entry), integrase strand transfer inhibitors (INSTIs) [8]. It was found that the treatment with one or two drugs has short therapy effect due to the rapid emergence of mutant forms of the virus with reduced susceptibility to antiretroviral drugs.…”
mentioning
confidence: 99%